2022
DOI: 10.1111/ans.18180
|View full text |Cite
|
Sign up to set email alerts
|

Reverse digital artery island flap with versus without sensory nerve coaptation for finger pulp reconstruction

Abstract: Purpose Whether an innervated reverse digital artery island flap is superior to a non‐innervated reverse digital artery island flap still remains controversial. We aimed to compare the clinical outcomes of the two flaps in repairing finger pulp soft tissue defects. Methods Medical records of patients who underwent finger pulp reconstruction between January 2007 and December 2017 were evaluated retrospectively. A total of 45 patients were included. Twenty underwent sensory nerve reconstruction with cutaneous br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The extent of sensory recovery of the non-insensate flap depends on the size of the flap and the extent of peripheral nerve regeneration around the flap [19]. Although previous studies had demonstrated that flaps larger than 1.0 × 1.0 cm had a reduced capacity for recovery of sensation without nerve coaptation, many studies obtained a protective 2-PD at a satisfactory level by using non-innervated flaps [20,21]. Although the innervated flap provided fairly rapid and satisfactory sensory recovery of the repair area, it caused noticeable sensory loss of the donor site on the dorsal side of the proximal or middle phalanges.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of sensory recovery of the non-insensate flap depends on the size of the flap and the extent of peripheral nerve regeneration around the flap [19]. Although previous studies had demonstrated that flaps larger than 1.0 × 1.0 cm had a reduced capacity for recovery of sensation without nerve coaptation, many studies obtained a protective 2-PD at a satisfactory level by using non-innervated flaps [20,21]. Although the innervated flap provided fairly rapid and satisfactory sensory recovery of the repair area, it caused noticeable sensory loss of the donor site on the dorsal side of the proximal or middle phalanges.…”
Section: Discussionmentioning
confidence: 99%